Advokasi Peran TuhaPeut Gampong dalam Formulasi Kebijakan Qanun Gampong - Ferizaldi Ferizaldi; Saharuddin Saharuddin; Muhammad Hasyem; Syamsuddin Syamsuddin; Ti Aisyah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The Tuha Peut institution is located as an element of gampong government administration and has the authority to form gampong qanuns together with the Geuchik, so its main duties and functions are very important, besides having other authorities in accordance with Aceh's specialties, but its current existence is especially in Gampong Teungoh Pirak, Matangkuli District, North Aceh It is not yet optimal and seems too focused on administrative aspects only, many problems at the gampong level have not been regulated by qanuns, several gampong qanuns should immediately be prioritized as gampong legislative products to answer various urgent problems. In this regard, advocacy or mentoring activities are needed to create a Tuha Peut institution that is effective in carrying out its main tasks and functions so that they are carried out well in accordance with its capacity as a community representative for the benefit of the gampong community. For flexibility in activities, advocacy is carried out using a dialogic and consultation model. so that it will create an atmosphere full of familiarity to produce positive and constructive thinking without being patronizing..